Six‐phase interleaved boost dc/dc converter with high‐voltage gain and reduced voltage stress. Issue 14 (1st November 2017) - Maalandish, Mohammad; Hosseini, Seyed Hossein; Ghasemzadeh, Saeed; Babaei, Ebrahim; Shalchi Alishah, Rasoul; Jalilzadeh, Tohid
Abstract : In this study, a new non‐isolated six‐phase interleaved boost dc–dc converter is presented for photovoltaic (PV) applications. The suggested structure consists of two symmetric three‐phase interleaved boost dc–dc converters along with two switched‐capacitor cells, in order to obtain high conversion ratio. For different values of duty‐cycles, the voltage conversion ratio of the proposed topology is high. Also, the voltage stress of switches for various duty cycles is low and the efficiency of proposed topology is high. Moreover, the value of input current ripple is low with the utilisation of interleaving techniques. These advantages cause the proposed topology to be a good candidate for PV systems. The operation modes and mathematical analysis of the presented converter is introduced. In order to show the merits of presented converter, comparison results with other boost dc/dc converters are provided. Both experimental and simulation works based 453 W are presented to verify the operation of recommended converter. PSCAD/EMTDC software is used for simulation work.